ASSESSING THE IMPACT OF CONTENT MARKETING, INFLUENCER MARKETING, AND ELECTRONIC WORD OF MOUTH ON SUBSIDIZED HOUSING PURCHASE DECISIONS: THE MODERATING EFFECT OF E-WOM - Budi Susanto; Yacob, Syahmardi; Lubis, Tona Aurora (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to examine the influence of Content Marketing, Influencer Marketing, and Electronic Word of Mouth (e-WOM) on purchase decisions for subsidized housing, as well as to evaluate the moderating role of e-WOM in the relationship between digital marketing strategies and consumer purchasing decisions. The research was conducted at PT. Digdaya Cipta Harjita, involving 190 respondents who had purchased subsidized housing in Jambi City and Muaro Jambi Regency. Employing a quantitative approach with Partial Least Square-Structural Equation Modeling (PLS-SEM), the results indicated that Content Marketing (β = 0.125; T = 2.117; p = 0.036), Influencer Marketing (β = 0.261; T = 3.195; p = 0.002), and e-WOM (β = 0.254; T = 3.012; p = 0.003) have a positive and significant impact on purchase decisions. Furthermore, e-WOM demonstrates a significant negative moderating effect on the relationship between Content Marketing and purchase decisions (β = –0.153; T = 2.314; p = 0.022), and a positive moderating effect on the relationship between Influencer Marketing and purchase decisions (β = 0.161; T = 2.067; p = 0.040). The model's R-square value of 0.267 indicates that the proposed variables explain 26.7% of the variance in purchasing decisions. These findings suggest that the effectiveness of digital marketing strategies in promoting subsidized housing is influenced not only by the quality of content and social influence but also by consumer perceptions shaped through digital word-of-mouth interactions, highlighting the critical role of online reputation management in enhancing marketing outcomes.